Neurosteroid Influences on Sensitivity to Ethanol - Helms, Christa M.; Rossi, David; Grant, Kathleen A. (Frontiers in Endocrinology, 2012)
Harrison and Simmonds (1984) provided the first clear evidence that neuroactive steroids act at specific neurotransmitter receptors, investigating the potentiation of muscimol-induced GABAA responses by alphaxalone (3α-hydroxy 5α -pregnane l l,20-dione) in cortical slices. Within 2 years, a progesterone metabolite (3α-hydroxy-5α-pregnan-20-one, 3α,5α-THP, allopregnanolone) and a deoxycorticosterone metabolite (3α,21-dihydroxy-5α-pregnan-20-one, 3α,5α-THDOC, tetrahydrodeoxycorticosterone, THDOC) were shown to be positive modulators of GABAA receptors (Majewska et al., 1986). That same year, publications showed that ethanol has direct action at GABAA receptors (Allan and Harris, 1986, Suzdak et al., 1986). Thus, the GABAA receptor complex was identified as a membrane-bound target providing a pharmacological basis for shared sensitivity between neurosteroids and ethanol. The common behavioral effects of ethanol and neuroactive steroids were compared directly using drug discrimination procedures (Ator et al., 1993). The N-methyl-D-aspartate (NMDA) receptor complex, a membrane-bound ionophore important for excitatory glutamate neurotransmission, was shown to be antagonized by low concentrations of ethanol (Lovinger et al., 1989). Since data were emerging for neurosteroid activity at NMDA receptors (Wu et al., 1991), the stage was set for the suggestion that neurosteroids, and physiological states that alter circulating neuroactive steroids, could affect sensitivity to alcohol (Grant et al., 1997). The unique interface of ethanol and neurosteroids encompasses molecular, cellular, physiological and behavioral processes. This review will highlight a variety of mechanisms by which neurosteroids affect sensitivity to ethanol, including metabolic pathways, physiological states associated with activity of the hypothalamic-pituitary adrenal (HPA) and hypothalamic-pituitary-gonadal (HPG) axes, and the effects of chronic exposure to ethanol, in addition to behavioral implications.